Sustainable HRM Practices and Employee Pro-Environmental Behavior: The Mediating Role of Environmental Commitment and the Moderating Role of Green Leadership - Dadang Heri Kusumah; Tri Wahyu Wirjawan; Dheni Eka Mahendra; Irma Rohmatul Manan (Fundamental and Applied Management Journal, 2026)
The increasing global emphasis on environmental sustainability and Environmental, Social, and Governance (ESG) practices has encouraged organizations to integrate sustainability principles into human resource management. In the manufacturing sector, employee participation is essential for achieving sustainability goals. However, the mechanisms through which Sustainable Human Resource Management (Sustainable HRM) Practices influence Employee Pro-Environmental Behavior remain insufficiently explored in emerging economy contexts. Therefore, this study examines the effect of Sustainable HRM Practices on Employee Pro-Environmental Behavior by investigating the mediating role of Environmental Commitment and the moderating role of Green Leadership. This quantitative explanatory study employed a cross-sectional survey approach. Data were collected from 150 employees of manufacturing companies using purposive sampling and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The structural model showed strong explanatory power, with R² values of 0.716 for Environmental Commitment and 0.719 for Employee Pro-Environmental Behavior. The results indicate that Sustainable HRM Practices significantly enhance Environmental Commitment (beta = 0.487) and Employee Pro-Environmental Behavior (beta = 0.422). However, Environmental Commitment had a statistically non-significant direct effect on Employee Pro-Environmental Behavior (beta = 0.135, p > 0.05), suggesting that psychological commitment alone may be insufficient to drive actual behavior without direct leadership intervention. Furthermore, Green Leadership marginally strengthened the relationship between Sustainable HRM Practices and Environmental Commitment (beta = 0.128, p = 0.052), indicating a boundary condition in attitude formation. This study contributes to sustainable HRM literature by emphasizing the need to couple formal HRM practices with strong green leadership, although findings should be interpreted cautiously due to the cross-sectional design and single-industry focus.